INNOVATION POLICY IN THE CONTEXT OF THE STRATEGY OF FINANCIAL AND ECONOMIC SECURITY OF ENTERPRISE - Mykhailiv , H.V.; Hryniv, L.V. (The actual problems of regional economy development, 2018)
In this article the general procedure of formation of innovation policy at the enterprise is considered. It was established that in order to implement effective innovation activities, it is necessary to develop an innovation policy in accordance with the order of its formation in the context of the strategy of financial and economic security. The authors proposed the following stages of formation of innovation policy: determining the relevance of the formation of innovation policy for the enterprise; assessment of innovative potential; formation of the strategy of innovative development of the enterprise in the guideline of financial and economic security; development of a program of innovation activity; creation of an innovation program evaluation system. Theoretical points as for definition of “financial-economical security” have been researched and summing up. The present attitude were analyzed as for the financial-economical enterprise security forming in the terms of unconformity and system attitude necessity stipulated for strategy system management by a financial-economical enterprise security.